Risk Factors for Reoperation in Patients Treated Surgically for Lumbar Stenosis: A Subanalysis of the 8 year data from the SPORT trial - Gerling, Michael C. (Spine (Phila Pa 1976), 2016)
STUDY DESIGN: A retrospective subgroup analysis was performed on surgically treated patients from the lumbar spinal stenosis (SpS) arm of the Spine Patient Outcomes Research Trial (SPORT), randomized and observational cohorts. OBJECTIVE: To identify risk factors for reoperation in patients treated surgically for SpS and compare outcomes between patients who underwent reoperation with those that did not. SUMMARY OF BACKGROUND DATA: SpS is the most common indication for surgery in the elderly; however, few long-term studies have identified risk factors for reoperation. METHODS: A post-hoc subgroup analysis was performed on patients from the SpS arm of the Spine Patient Outcomes Research Trial (SPORT), randomized and observational cohorts. Baseline characteristics were analyzed between reoperation and no reoperation groups using univariate and multivariate analysis on data eight years post-operation. RESULTS: Of the 417 study patients, 88% underwent decompression only, 5% non-instrumented fusion and 6% instrumented fusion. At the 8 year follow up, the reoperation rate was 18%; 52% of reoperations were for recurrent stenosis or progressive spondylolisthesis, 25% for complication or other reason and 16% for new condition. Of patients who underwent a reoperation, 42% did so within 2 yrs, 70% within 4 years and 84% within 6 years. Patients who underwent reoperation were less likely to have presented with any neurological deficit (43% reop vs. 57% no reop, p=0.04). Patients improved less at follow-up in the re-operation group (p<0.001). CONCLUSION: In patients undergoing surgical treatment for SpS, the reoperation rate at eight year follow-up was 18%. Patients with a reoperation were less likely to have a baseline neurological deficit. Patients who did not undergo reoperation had better patient reported outcomes at eight year follow up compared to those who had repeat surgery.